THE BRAND IMAGE OF EXPEDITION COMPANIES IN INDONESIA : A CORRESPONDENCE ANALYSIS - Irwansyah Irwansyah; Resista Vikaliana (Jurnal Logistik Indonesia, 2018)
The purpose of this analysis is to determine the relevant attributes that meet the perceived similarity between objects four expedition companies in Indonesia consist of: JNE, Tiki, J&T and PT Posindo, and determine the preference of the category of variables that determine the attributes and categories of objects. The data used in this research is primary data using questionnaire research instrument.Correspondence analysis is used to analyze the data collected.   Correspondence analysis is a technique of data presentation between rows, between columns and between rows and columns of contingency tables (two-way which can then be extended to multi-way contingency table) at a small-dimensional vector space and optimal. This analysis is also designed to be used in the development of groupings that represent the data frequency. The results of correspondence analysis found that the JNE brand is close to the tariff image. The Tiki and J&T brands are close to on time delivery. While the brand Posindo is not close to any image.